Study of Alternative Inundation Management Based on Water Conservation in Sub Drainage System of Parung River, Kediri City - Nugroho, Himawan Dwi; Bisri, Mohammad; Wahyuni, Sri (Journal of Applied Science, Engineering, Technology, and Education, 2023)
Parung River drainage sub system is located in Kediri City. At the peak of the rainy season inundation often occurs on hos cokroaminoto road, kilisuci road and terusan kaliombo road, the cause is reduced water catchment areas and drainage capacity can’t accommodate discharge, so it is necessary to handle water conservation-based inundation. The analysis conducted was modelling the sub-system using the Storm Water Management Model (SWMM) version 5.1 with a 5-year return period. Rainfall calculation used 10 years of daily rain data (2012-2021) from 3 rain stations (Mrican, UPT Kediri, and Pesantren). The 5-year return period results is 129.4 mm/day, then the intensity of rain is calculated using the Mononobe formula. To calibrate the model, comparing observation discharge with simulated discharge of SWMM resulted the Nash-Sutcliffe efficiency number is 0.62 and the correlation R is 0.91. The results of the existing simulation show that Parung River drainage sub-system was not able to accommodate the 5-year return period discharge, impacting 27 overflow points. Water conservation based handling with the application of infiltration wells and rainwater harvesting can reduce discharge on land ranging from 51.58% to 90.91%, while in the channel successfully reduces discharge from 1.73% to 90.40%.